Die deutsche Bibelübersetzung des Mittelalters - Walther, Wilhelm, (European History and Culture - Book Archive pre-2000, 1966)
Basic work on German Bible- and Psalter translations during the Middle Ages. Examines several hundred manuscripts and early printed editions and identifies over seventy active Bible translators. Includes excerpts of each translation as well.